Uncovering the complexities of biological structures with network-based learning: An application in SARS-CoV-2 - Faghri, Faraz (Patterns (N Y), 2021)
Network-based learning enables the identification of possible undiscovered interactions in biological systems. In this issue of Patterns, Du et al. show that applying these methods to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) reveals potential infection targets of the virus and possible interactions between SARS-CoV-2 proteins and human proteins.